Find the constellations - Rey, H. A. (Hans Augusto), 1898-1977 (Houghton Mifflin Harcourt, 2008)
This second edition of Find the Constellation contains star charts, a guide to the constellations, and details about seasons and the movement of the objects we see in the sky with planetary and solar system information in the latter part of the book. Facts and figures for each planet have been revised, and new scientific information has been added, such as Pluto's reclassification as a dwarf planet.